Dietary Diversity and Associated Factors Among Pregnant Women in Addis Ababa, Ethiopia, 2021 - Aynshet Nega Kebede; Addisu Tadesse Sahile; Bethlehem Chala Kelile (Frontiers Media S.A., 2022)
Objective: This study aimed to assess the dietary diversity and its associated factors among pregnant women in Addis Ababa, Ethiopia, 2021.Methods: An institution-based Cross-sectional was conducted among 320 participants from four health facilities in Addis Ababa selected based on a simple random sampling method from 01 September to 30 December 2021. An Interviewer-administered structured questionnaire was used, following informed consent. Binary (Bivariate and multivariate) logistics regression was applied for the identification factors associated with dietary diversity with their respective 95% confidence interval and less than 5% p-value.Results: The prevalence of inadequate dietary diversity during pregnancy was 51.6% (95% CI: 46.1%-57.0%). Being illiterate (AOR: 0.591; 95% CI: 1.88-1.901; p < 0.05) and primary education (AOR: 0.347; 95% CI: 0.166-0.728; p < 0.05), having poor knowledge (AOR: 0.437; 95% CI: 0.252-0.757; p < 0.05) and lower monthly income (AOR: 0.395; 95% CI: 0.184-0.845; p < 0.05) were factors associated with inadequate dietary diversity.Conclusion: A higher level of inadequate dietary diversity was reported. Being illiterate, having primary education, having poor knowledge, and having lower monthly income were associated with inadequate dietary diversity during pregnancy. Concerned bodies were suggested to work on the identified factors.